Identification of Technical Characteristics of Ergonomic Baby Dining Chair Products - Fithri, Prima; Syafruddin Indrapriyatna, Ahmad; Syaddad Hamdan , Farrell; Handayani Gusmira , Yuni (LPPM Universitas Andalas, 2025)
This research aims to design an ergonomic toddler dining chair that meets the needs of safety, comfort, and usability for families, restaurants, and daycare centers in Padang City. The study identifies deficiencies in existing products and proposes solutions that suit user preferences and ergonomic standards. This research utilizes a mixed-method approach, starting with the Kano model to classify user needs into categories such as